Automated Generation of End-to-End Web Test Cases via a Generic AI Agent: A Comparative Study of DeepSeek V3 and Claude Sonnet 4 - Monteiro, Caio E. O.; Guerino, Lucca R.; Fernandes, Guilherme F.; Pereira, Marcos H.; Souza-Zinader, Juliana P. de; Braga, Renata D.; Pocivi, Viviane C. B.; Vincenzi, Auri M. R. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2025: Proceedings of the 31st Brazilian Symposium on Multimedia and the Web, 2025)
Web applications are widespread and can be accessed from anywhere, in theory, using aweb browser on a computer or smartphone. Primarily due to the diversity of web browsers and frameworks available for developing web application interfaces, testing such applications is a challenging task. With the advent of large language models, several works are utilizing them to automate software engineering tasks, including test case generation. This use of LLMs for test case generation prioritizes unit testing. More recently, we have seen the advent of Generic Artificial Intelligence Agents, which are tools that utilize LLMs and also possess the ability to run additional tools, such as cloning repositories, navigating websites, and compiling programs. In this work, which is part of a research and development project, we evaluate a specific Generic AI Agent Assistant regarding its capability to navigate web applications and create fully automated end-to-end test cases, utilizing Selenium WebDriver and JUnit 5 framework. Results show that, considering a set of nine websites, in overall end-to-end test case generation, Suna configured with DeepSeek V3 produced 165 successful test cases out of 481 generated tests, a success rate of 34.3%. On the other hand, Suna configured with Claude Sonnet 4 produced 336 successful test cases out of 479 generated tests, a success rate of 70.1%, which is very impressive, mainly due to the complexity of creating end-to-end testing. In terms of cost, we used a free and a paid LLM model. The paid model generates successful test cases at an average price of $ 0.15 per test case.